Judgments About Male Victims of Sexual Assault by Women: A 35-Year Replication Study - PeConga, Emma K. (Journal of interpersonal violence, 2022)
Sexual assault of men by women has received increasing attention in recent years, as has research on rape myths about male victims. This study is a cross-generational replication of a 1984 study of college students? judgments about male and female victims in a scenario involving a sexual assault carried out by male or female assailants. The 1984 data (n = 172) were compared with those of a 2019 cohort (n = 372) in a 2 (participant gender) x 2 (assailant gender) x 2 (victim gender) x 2 (cohort) factorial design to assess potential generational changes in perceptions of victims. Judgments by male participants of male victims of assaults carried out by women changed notably over time. The 2019 male cohort was less likely to judge that the victim initiated or encouraged the incident (40% in 1984 compared with 15% in 2019) and derived pleasure from it (47.4% in 1984 compared with 5.8% in 2019). In contrast, the 2019 female cohort was more likely to attribute victim encouragement (26.9% compared with 4.3% in 1984) and pleasure to the male victim (25% in 2019 compared with 5% in 1984). A similar gender pattern occurred in judgments of how stressful the event was for the male victim. Analysis of the 2019 data revealed that overall, despite scientific and cultural shifts that have occurred over the past three decades, participants continued to judge the male victim of assault by a female to have been more encouraging and to have experienced more pleasure and less stress than in any other assailant/victim gender combination. Results are discussed in relation to gendered stereotypical beliefs and male rape myths, as well as possible sensitization to power differentials inspired by the #MeToo movement. We emphasize the need for greater awareness and empirical attention to abuse that runs counter to preconceived notions about sexual victimization.